Reactive and Proactive Aggression and Suicide Attempts Among Criminal Offenders. (March 2014) - Swogger, Marc T.; Walsh, Zach; Maisto, Stephen A.; Conner, Kenneth R.
Outwardly directed aggression is associated with suicide attempts, but aggression is a heterogeneous construct. Increased specificity in our understanding of the link between aggression and suicide attempts can be attained by examining subtypes of aggression. We studied the relationships of reactive and proactive aggression to history of a suicide attempt among 96 criminal offenders in a pretrial supervision program. Consistent with prior findings in nonoffender samples, reactive aggression was associated with a history of suicide attempt after controlling for gender and depression. Proactive aggression was unrelated to suicide attempts. Results indicate that suicide risk assessments in forensic settings may be informed by the measurement of reactive aggression.